Radiological assessment of pulmonary vascular changes and gastrointestinal changes in patients with COVID-19 referred to a tertiary health care center in Chennai, India: a prospective cross-sectional study - Hariharan Sathishkumar; Afwaan Faizal; Abdul Majith; Vishnu Raj; Agathiyanathan Venkataramani (Digital Diagnostics)
BACKGROUND: The coronavirus disease pandemic (COVID-19), caused by severe acute respiratory syndrome coronavirus 2, has led to significant morbidity and mortality worldwide since its emergence in 2019. Although primarily a respiratory illness, COVID-19 can also affect other organ systems, including the vascular and gastrointestinal systems. COVID-19 is linked to both venous and arterial thrombosis, and numerous studies have indicated a heightened risk of pulmonary embolism. Autopsies have revealed pulmonary vasculature thrombosis and bowel ischemia in patients with COVID-19.